Belowground Dynamics Influence Nitrogen Cycling and Crop Productivity in Diversified Corn Systems - Martin, Tvisha; Sprunger, Christine D. (Frontiers in Sustainable Food Systems, 2021)
Ecological nutrient management is a strategy that can help create resilient cropping systems and reduce the negative impact that agricultural systems have on the environment. Ecological nutrient management enhances plant-soil-microbial interactions and optimizes crop production while providing key ecosystem services. Incorporating perennial legumes into crop rotations and implementing no-till to enhance organic nitrogen (N) soil pools could reduce the need for inorganic N fertilizer inputs and lead to improved soil health. Plant and soil N pools need to be further quantified to understand how to enhance soil health across a range of agroecosystems. This paper aims to quantify plant and soil N pools in systems contrasting in crop perenniality (corn–corn, corn–soy, and corn–forage–forage) and tillage intensity (chisel till vs. no-till). Key plant, soil, and organismal metrics of N cycling were measured including fine root production, N-Acetyl-B-Gulcosaminidase (NAG) enzyme activity, and soil protein, nematode enrichment opportunist (fungal and bacterial feeding nematodes) and the nematode Enrichment Index. Fine root production was determined using in-growth mesh cores. Findings reveal that monoculture cropping systems with reduced tillage intensity and rotations with perennial legumes had significantly greater fine root N (FRN), soil protein and NAG enzyme activity (p < 0.05) relative to corn-soy. Additionally, nematode bacterivore enrichment opportunists (b1) were significantly reduced in corn-corn systems when compared to all other crop rotation systems. Correlation analyses indicated positive and significant relationships between FRN and soil protein (p < 0.05). These results demonstrate that lengthening crop rotations with perennial legumes and incorporating no-till management can increase organic N inputs, N mineralization rates, and organic N storage. Such ecological approaches to management have the potential to reduce the need for inorganic N inputs, while increasing long-term soil health and crop productivity.